Aedes aegypti as potential vector of filariasis in Pekalongan, Central Java Province, Indonesia - Siti Istianah; Budi Mulyaningsih; Sitti Rahmah Umniyati; Eggi Arguni (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2021)
Background: The filariasis elimination program in Indonesia has been conducted, but new cases and some chronic cases are still often found.Objective: This study aims to determine levels of endemicity and to identify filarial worm species in filariasis cases and s and their surrounding communities by using microscopic examination, polymerase chain reaction (PCR), and to examine levels of infection in vectors mosquito by surgery and PCR. Also to to determine that Ae. aegypti can act as vector of filariasis. Methods: This study was conducted at 10 locations in Pekalongan Regency, Central Java Province, with a cross sectional design. Intravenous blood sampling was conducted on 102 respondents consisting of 10 elephantiasis patients and 92 non-elephantiasis patients at night, starting at 8 pm, then examined microscopically and PCR. Mosquitoes in this study were collected by using a human landing collection method for 12 hours from 6 pm to 6 am by volunteers. Artificial infection of microfilaria W. bancrofti was held against Cx. quinquefasciatus and Ae.aegypti from laboratory collection.Results: Results of this study found that there were 5.729 of mosquitos, consisting of 8 species, namely Culex quinquefasciatus, Culex vishnui, Culex tritaeniorhynchus, Aedes aegypti, Aedes albopictus, Anopheles subpictus, Anopheles vagus, and Armigeres kesseli. Microfilarial (mf) rate was 0.89%, and and the blood PCR showed infection rate of 3.92% and the blood PCR showed infection rate of 3.92%. No larva was found in female mosquito dissection. The PCR results showed that the infection rate was 9.10% in Ae. aegypty pool respectively. Artificial infection results was negative both dissecting microscopis and PCR.Conclusion: This study revealed that the locations were low of filariasis endemicity. The mf rate was less than 1%, and there was a moderate density to high density of microfilaria in the patients. The low level of infection rates in mosquito is suggested as an alert to its potential transmission.